Harnessing Artificial Intelligence: Pioneering Opportunities for Aspiring Entrepreneurs - Hegde, Kavya P.; Nayak, Venkatesha (Universitas Sarjanawiyata Tamansiswa, 2024)
The rapid advancement of Artificial Intelligence (AI) is reshaping entrepreneurship by offering new opportunities for innovation and market disruption. This study explores AI’s role in fostering entrepreneurial ventures by reducing uncertainty, enhancing decision-making, and enabling data-driven strategies. The research aims to examine how AI facilitates entrepreneurial opportunities, supports informed decision-making, and impacts business performance. A mixed-methods approach was employed, incorporating a systematic literature review, survey data from 114 entrepreneurs using AI, and semi-structured interviews with industry experts. Statistical and thematic analyses assessed AI's impact on entrepreneurial success. Findings indicate that AI enhances opportunity identification, improves strategic decision-making, and contributes to business growth. Entrepreneurs utilizing AI reported a 12.5% average revenue increase compared to 7.3% for non-AI firms and improved operational efficiency and customer satisfaction. However, challenges such as cost barriers, ethical concerns, and regulatory constraints were noted, particularly for small businesses. AI serves as a transformative tool for entrepreneurship, driving innovation and competitiveness. However, equitable access, regulatory balance, and responsible adoption remain critical for sustainable growth. Future research should explore scalable AI integration strategies to support diverse entrepreneurial ecosystems.